2016
DOI: 10.1097/pts.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patient Characteristics Associated With Deficits in Surgical Decision Making

Abstract: Background Patient involvement in surgical decisions is formalized in the informed consent process, which should reflect that the patient understands their diagnosis, planned procedure, and the associated risks and benefits before consenting to treatment. If high-quality shared decision making has occurred, the treatment chosen should best match the goals and preferences of the patient. Little information currently exists that analyzes factors associated with decisional quality in surgery. Identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…We also want to develop ways to standardize how we interpret patients’ care wishes and assess their support system and resources, which may be implemented into the HRC meeting. It has been shown that patients have deficits in surgical decision making . The recommendations of the HRC may be a useful tool for education and a starting point for goals of care discussion for patients and their families.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also want to develop ways to standardize how we interpret patients’ care wishes and assess their support system and resources, which may be implemented into the HRC meeting. It has been shown that patients have deficits in surgical decision making . The recommendations of the HRC may be a useful tool for education and a starting point for goals of care discussion for patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that patients have deficits in surgical decision making. 13,14 The recommendations of the HRC may be a useful tool for education and a starting point for goals of care discussion for patients and their families. We also would like to design a study looking at the impact of the HRC on ACS-NSQIP results at our institution in a prospective manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Among other factors, higher age has been shown to be associated with deficits in surgical decision making. 6 Multidimensional patient-centred approaches 7 and best communication practices 8,9 have been discussed to facilitate decision making in elderly patients with surgical emergencies. Recent studies investigated outcomes of patients >80 years of age undergoing cardiovascular or neurosurgical interventions.…”
Section: Introductionmentioning
confidence: 99%